Multi-approach model for improving agrochemical safety among rice farmers in Pathumthani, Thailand - Siriwong W; Robson M; Raksanam B; Taneepanichskul S (Dove Medical Press, 2012)
Buppha Raksanam,1,2 Surasak Taneepanichskul,2 Wattasit Siriwong,2 Mark Robson3,41Sirindhorn College of Public Health, Trang, 2College of Public Health Sciences, Chulalongkorn University, Bangkok, Thailand; 3School of Environmental and Biological Sciences, Rutgers University, 4School of Public Health, University of Medicine and Dentistry of New Jersey, New Brunswick, NJ, USAAbstract: The large-scale use of agrochemicals has raised environmental and human health concerns. A comprehensive intervention strategy for improving agrochemical safety among rice farmers in Thailand is lacking. The objective of this study is to develop a model in order to improve farmers’ health and prevent them from being exposed to agrochemical hazards, in addition to evaluating the effectiveness of the intervention in terms of agrochemical safety. This study was conducted between October 2009 and January 2011. It measures changes in the mean scores of agrochemical knowledge, health beliefs, agrochemical use behaviors, and in-home pesticide safety. Knowledge of agrochemical use constitutes a basic knowledge of agrochemicals and agrochemical safety behaviors. Health beliefs constitute perceived susceptibility, severity, benefits, and barriers to using agrochemicals. Agrochemical use behaviors include self-care practices in terms of personal health at specific times including before spraying, while spraying, during storage, transportation, waste management, and health risk management. Fifty rice farmers from Khlong Seven Community (study group) and 51 rice farmers from Bueng Ka Sam community (control group) were randomly recruited with support from community leaders. The participants were involved in a combination of home visits (ie, pesticide safety assessments at home) and community participatory activities regarding agrochemical safety. This study reveals that health risk behaviors regarding agrochemical exposure in the study area are mainly caused by lack of attention to safety precautions and the use of faulty protective gear. After 6 months, the intervention program showed significant improvements in the overall scores on knowledge, beliefs, behaviors, and home pesticide safety in the study group (P < 0.05). Therefore, this intervention model is effective in improving agrochemical safety behaviors among Khlong Seven Community rice farmers. These findings demonstrate that a multi-approach model for improving agrochemical safety behaviors can lead to sustainable prevention of agrochemical hazards for farmers.Keywords: rice farmer, agrochemical safety, community-based intervention, model